Penerapan Problem Based Learning dalam Penelitian Tindakan Kelas Untuk Meningkatkan Motivasi dan Hasil Belajar Biologi Pada Peserta Didik Kelas X SMA Negeri 3 Palu - Sari, Maya; Tangge, Lilies; Mahyuddin, Mahyuddin (Jurnal sosial dan sains, 2025)
This research aims to improve the motivation and learning outcomes of Biology through the application of the Problem Based Learning (PBL) learning model in class X students of SMA Negeri 3 Palu. The type of research used is Class Action Research (PTK) which is carried out in two cycles with four stages: planning, implementation, observation, and reflection. The research subjects consisted of 35 students in classes X-L. Data were collected using learning motivation questionnaires and learning outcome tests, then analyzed in a quantitative descriptive manner. The results showed that the application of PBL can increase students' motivation to learn, most of which are in the categories of high motivation (63.6%–80.4%) and very high (81.4%–100%). In addition, student learning outcomes also increased, with an average score from 66 in the first cycle to 81.29 in the second cycle, and classical completeness increased from 28.6% to 85.71%. Thus, the application of PBL has been proven to be effective in increasing the motivation and learning outcomes of Biology students in class X of SMA Negeri 3 Palu.